Sustainability of pondok warga emas according to needs and interests as an islamic tourism destination in Malaysia - Norhayati Rafida Abdul Rahim; Norailis A.W.; Safiyyah A.S.; Awais I.A.; Ab Rahman Z. (Innovare Academics Sciences Pvt. Ltd, 2024)
Indexed by Scopus